2020
DOI: 10.1111/anu.13158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of differential protein levels of feed on growth, copper‐induced immune response and oxidative stress of Rhynchocypris lagowski in a biofloc‐based system

Abstract: This study compared the influences of differential protein levels of feed on growth, copper-induced digestive enzyme activity, immune response, oxidative stress and Nrf2 signalling molecules genes expression of Rhynchocypris lagowski in a bioflocbased system and traditional autotrophic system. Four hundred and fifty R. lagowski were fed four experimental dietary containing graded levels of protein from 25% to 37% (referred as biofloc technology [BFT]25, BFT29, BFT33 and BFT37, respectively) in a biofloc-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Indeed, dietary supplements may have a better advantage in improving the fish immune response or control the severity of infection (Menanteau‐Ledouble et al, 2017). The biological trial has demonstrated that dietary supplements are the key source to maintain optimal growth and health of fish, which have high biocompatibility and sustainability (Wu et al, 2019; Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, dietary supplements may have a better advantage in improving the fish immune response or control the severity of infection (Menanteau‐Ledouble et al, 2017). The biological trial has demonstrated that dietary supplements are the key source to maintain optimal growth and health of fish, which have high biocompatibility and sustainability (Wu et al, 2019; Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They can recognize denatured proteins, assist protein repair, stimulate immunity, reduce oxidative damage and play a protective role (Li, Li, et al., 2019; Roberts et al., 2010). Interferon‐γ can effectively block the invasion of pathogens, along with a variety of immune enzymes, to resist virus infection (Yu, Zheng, et al, 2020b). IGF‐1 is a necessary active protein polypeptide in the physiological process of growth hormone production, and it has the laudatory name “growth hormone medium” (Chen et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Growth index and muscle nutrient composition (e.g. WGR, SGR, feed conversion rate [FCR], protein efficiency rate [PER], hepatosomatic index [HI], viscerasomatic index [VI], condition factor [CF], moisture, ash, crude lipid and crude protein) were measured, with reference to our previous study (Yu, Quan, et al., 2020; Yu, Zheng, et al., 2020b). Second, the gill, kidney, hepatopancreas and gut were removed quickly from each living fish by vivisection on a liquid nitrogen cold plate; the tissues were washed with ice‐cold double‐distilled water, cut into pieces and mixed with physiological saline at 1:9 (W:V).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations